BL_GERICHTE 720 2012 340 / 77 vom 21. August 2007 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht vom 18. April 2013 (720 12 340 / 77) - BL Gerichte (2007)
IV-Rente